RAPID PROTOTYPING OF EMBEDDED PROGRAMMABLE SYSTEMS ON FPGA FOR MULTIMEDIA APPLICATIONS - V. V. Kliuchenia; N. A. Petrovsky (Informatika)
This paper illustrates rapid prototyping method applied for mobile multimedia systems with L2L (lossless-to-lossy) compression scheme. Debug module Xilinx ML-401 based on the FPGA (Filed Programmable Gate Array) is taken as the basis. Microblaze soft-processor is used as the main control unit. Proposed DCT-IDCT cores are developed using VHDL hardware description language as FSL (Fast Simples Link) coprocessors for Microblaze or standalone PLB (Processor Logical Bus) acceleration peripheral. Result of image processing is displayed on the screen connected via VGA interface. Proposed recursive architecture of DCT-IDCT core can be used as a basis of L2L coder.